Unusually Large Effects of Charge‐assisted C−H⋅⋅⋅F Hydrogen Bonds to Anionic Fluorine in Organic Solvents: Computational Study of 19F NMR Shifts versus Thermochemistry - Prof. Dr. Martin Kaupp; Caspar J. Schattenberg; Dr. Robert Müller; Marc Reimann (ChemistryOpen, 2022)
Abstract A comparison of computed 19F NMR chemical shifts and experiment provides evidence for large specific solvent effects for fluoride‐type anions interacting with the σ*(C−H) orbitals in organic solvents like MeCN or CH2Cl2. We show this for systems ranging from the fluoride ion and the bifluoride ion [FHF]− to polyhalogen anions [ClFx]−. Discrepancies between computed and experimental shifts when using continuum solvent models like COSMO or force‐field‐based descriptions like the 3D‐RISM‐SCF model show specific orbital interactions that require a quantum‐mechanical treatment of the solvent molecules. This is confirmed by orbital analyses of the shielding constants, while less negatively charged fluorine atoms (e. g., in [EF4]−) do not require such quantum‐mechanical treatments to achieve reasonable accuracy. The larger 19F solvent shift of fluoride in MeCN compared to water is due to the larger coordination number in the former. These observations are due to unusually strong charge‐assisted C−H⋅⋅⋅F− hydrogen bonds, which manifest beyond some threshold negative natural charge on fluorine of ca. < −0.6 e. The interactions are accompanied by sizable free energies of solvation, in the order F−≫[FHF]−>[ClF2]−>[ClF4]−. COSMO‐RS solvation free energies tend to moderately underestimate those from the micro‐solvated cluster treatment. Red‐shifted and intense vibrational C−H stretching bands, potentially accessible in bulk solution, are further spectroscopic finger prints.